THE INFLUENCE OF CORPORATE GOVERNANCE AND BOARD CHARACTERISTICS ON CSRD IN SRI-KEHATI INDEX FOR 2018-2022 - Amelia Amelia; Hendro Lukman; Sriwati Sriwati (Graduate Program of Universitas Tarumanagara, 2024)
The Good Corporate Governance can ensure that the company is managed in a responsible and transparent manner, including Corporate Social Responsibility (CSR). Several companies have expressed a form of Social Responsibility towards all stakeholders, including society, the environment and workers. One of the parties responsible for CSR disclosure is the board of directors. The characteristics possessed by directors can influence the company's commitment to CSR and the company's desire to disclose CSR information to the public. This research aims to analyze the influence of corporate governance and directors' characteristics on CSR disclosure in the Sri-Kehati Index for the 2018-2022 period. This research was analysed using multiple regression method which processed using SPSS 25. The data used in this research was secondary data from annual reports. This research used purposive-sampling technique with sample of 70 data observations. The results of this research show that the audit committee, independent commissioner, institutional ownership, managerial ownership, age of directors, gender of directors have no influence on CSR Disclosure. It can be concluded that the CSR information in the CSR Disclosure has been prepared without interference from the Board of Directors, Shareholders and Supervision of the Commissioners. The implications of this research show that CSR information which aims to provide CSR information in the context of sustainability, should be prepared professionally with adequate corporate governance.